Regularities of the formation of comutagenesis in irradiated human somatic cells - Pylypchuk, O.P.; Domina, E. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The pattern (regularity) of co-mutagenic effects formation in healthy individuals' irradiated cells (T-lymphocytes) under verapamil and ascorbic acid treatment is studied. It is determined that the additional action of the investigated drugs in concentrations greater than the therapeutic one potentiate the effects of low doses of ionizing radiation by 1.5 times. Ascorbic acid and verapamil show co-mutagenic effects under high-dose irradiation (2.0 Gy), increasing the chromosomal aberration level by 1.4 times, regardless of the concentration of drugs.